Enlaces Conjugais: amor tecido de laços ou de nós? Porto Alegre 2018 - Gonçalves, Kamila Baldino (Universidade do Vale do Rio dos Sinos, 2018)
This academic article seeks to deepen some important concepts regarding love relationships, more punctually at the choice of a loving partner, and still examine which elements are present in this complex process. This research will be carried out through a specific literature review and theoretical approximations with fragments of reports obtained in the practice of clinical listening of analytical orientation performed by the author. Finally the conclusions will be presented in a way to demonstrate the relevance of the understanding of this theme to the life of the individuals but mainly for psychologists and other professionals who work using clinical listening as a tool.
Keywords: Amor; Enlace conjugal; Escolha amorosa; Freud; Psicanálise; Love; Marital bond; Loving choise; Freud; Psychoanalysis